Coronary Artery Calcium Assessed Years Before Was Positively Associated With Subtle White Matter Injury of the Brain in Asymptomatic Middle-Aged Men: The Framingham Heart Study. (July 2021) - Suzuki, Harumitsu; Davis-Plourde, Kendra; Beiser, Alexa; Kunimura, Ayako; Miura, Katsuyuki; DeCarli, Charles; Maillard, Pauline; Mitchell, Gary F.; Vasan, Ramachandran S.; Seshadri, Sudha; Fujiyoshi, Akira
Abstract : Background: Using magnetic resonance diffusion tensor imaging, we previously showed a cross-sectional association between carotid-femoral pulse wave velocity, a measure of aortic stiffness, and subtle white matter injury in clinically asymptomatic middle-age adults. While coronary artery calcium (CAC) is a robust measure of atherosclerosis, and a predictor of stroke and dementia, whether it predicts diffusion tensor imaging-based subtle white matter injury in the brain remains unknown. Methods: In FHS (Framingham Heart Study), an observational study, third-generation participants were assessed for CAC (2002–2005) and brain magnetic resonance imaging (2009–2014). Outcomes were diffusion tensor imaging-based measures; free water, fractional anisotropy, and peak width of mean diffusivity. After excluding the participants with neurological conditions and missing covariates, we categorized participants into 3 groups according to CAC score (0, 0 < to 100, and >100) and calculated a linear trend across the CAC groups. In secondary analyses treating CAC score as continuous, we computed slope of the outcomes per 20 to 80th percentiles higher log-transformed CAC score using linear regression. Results: In a total of 1052 individuals analyzed (mean age 45.4 years, 45.4% women), 71.6%, 22.4%, and 6.0% had CAC score of 0, 0 < to 100, and >100, respectively. We observed a significant linear trend of fractional anisotropy, but not other measures, across the CAC groups after multivariable adjustment. In the secondary analyses, CAC was associated with lower fractional anisotropy in men but not in women. Conclusions: CAC may be a promising tool to predict prevalent subtle white matter injury of the brain in asymptomatic middle-aged men. Abstract : Supplemental Digital Content is available in the text.